Impact of Westernized Diet on Gut Microbiota in Children on Leyte Island - Nakayama, Jiro; Yamamoto, Azusa; Palermo-Conde, Ladie A.; Higashi, Kanako; Sonomoto, Kenji; Tan, Julie; Lee, Yuan-Kun (Frontiers in Microbiology, 2017)
Urbanization has changed life styles of the children in some towns and cities on Leyte island in the Philippines. To evaluate the impact of modernization in dietary habits on gut microbiota, we compared fecal microbiota of 7 to 9-year-old children from rural Baybay city (n = 24) and urban Ormoc city (n = 19), and assessed the correlation between bacterial composition and diet. A dietary survey indicated that Ormoc children consumed fast food frequently and more meat and confectionary than Baybay children, suggesting modernization/westernization of dietary habits. Fat intake accounted for 27.2% of the total energy intake in Ormoc children; this was remarkably higher than in their Baybay counterparts (18.1%) and close to the upper limit (30%) recommended by the World Health Organization. Their fecal microbiota were analyzed by high-throughput 16S rRNA gene sequencing in conjunction with a dataset from five other Asian countries. Their microbiota were classified into two enterotype-like clusters with the other countries’ children, each defined by high abundance of either Prevotellaceae (P-type) or Bacteroidaceae (BB-type), respectively. Baybay and Ormoc children mainly harbored P-type and BB-type, respectively. Redundancy analysis showed that P-type favored carbohydrates whereas BB-type preferred fats. Fat intake correlated positively with the Firmicutes-to-Bacteroidetes (F/B) ratio and negatively with the relative abundance of the family Prevotellaceae/genus Prevotella. A species-level analysis suggested that dietary fat positively correlated with an Oscillibacter species as well as a series of Bacteroides/Parabacteroides species, whereas dietary carbohydrate positively correlated with Dialister succinatiphilus known as succinate-utilizing bacteria and some succinate-producing species of family Prevotellaceae, Veillonellaceae, and Erysipelotrichaceae. We also found that a Succinivibrio species was overrepresented in the P-type community, suggesting the syntroph via hydrogen and succinate. Predicted metagenomics suggests that BB-type microbiota is well nourished and metabolically more active with simple sugars, amino acids, and lipids, while P-type community is more involved in digestion of complex carbohydrates. Overweight and obese children living in Ormoc, who consumed a high-fat diet, harbored microbiota with higher F/B ratio and low abundance of Prevotella. The altered gut microbiota may be a sign of a modern diet-associated obesity among children in developing areas.